Beyond the glass ceiling: work/home conflict, networking and mentoring as determinants of females’ career path to academic leadership in Nigerian universities (2006)
Researchers have eulogized the fact that women have indeed broken the glass ceiling as far as being represented in ‘enclaves’ thought to be the exclusive preserve of men. These enclaves had hitherto included positions of leadership, politics, and boards, professions such as engineering, sciences, technology and indeed higher education. Many of the women who have broken the glass ceiling, have through ‘thick and thin’ gone a long way to prove their worth in managing positions such as that of Vice-chancellors, deputies, Deans in higher education, politics and so on, but researches have, found out that the ‘Top’ is still a ‘chilly climate’ for women who aspire to be leaders especially in the academic environment. Even though women are being represented, the numbers are not significant and this makes the academic environment a masculine one. Many researchers have considered the areas of gender differences as key factors responsible for the dearth of women in leadership. In spite of gender, many women have managed to break through the glass ceiling, and are faced with challenges and experiences different from those of male colleagues. The paper seeks to find out what is happening after the glass ceiling. For women who are already there, what are the influences of home & work, networking and mentoring to their career path to leadership? What are the consequences of the presence or absence of these variables? The research generated data through in depth interviews with 25 female lecturers from different faculties and on different professional career cadre. Strong mentoring of women by women and committed men, creation of informal networks, ability to cope with executive stress and supportive home fronts are some of the strategies suggested.